2018
DOI: 10.47067/ramss.v1i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Style as a Cognitive Factor in Developing Big-Five Personality Traits among Youth: A Study of Public University in Multan, Pakistan

Abstract: The present study aimed to investigate the relationship between parenting styles (authoritarian, authoritative and permissive) and Big-five personality traits (extraversion, agreeableness, neuroticism, conscientiousness and openness) among the students of Bahauddin Zakariya University Multan, Pakistan. For this purpose, a total number of 281 students from different faculties (Natural and social sciences) were selected through systematic sampling technique and the respondents responded to parenting authority qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Regarding the psychological and social genesis of the emotional state of adolescents, there seems to be a certain consensus on the influence of the family on adolescents' knowledge of themselves, on their self-esteem, social skills, prosociality, and, ultimately, in the development of emotional intelligence [21][22][23][24][25][26][27][28][29]. Of course, the educational system also plays a relevant role in shaping the perceptions of adolescents, as well as in the development of their potentialities and difficulties [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the psychological and social genesis of the emotional state of adolescents, there seems to be a certain consensus on the influence of the family on adolescents' knowledge of themselves, on their self-esteem, social skills, prosociality, and, ultimately, in the development of emotional intelligence [21][22][23][24][25][26][27][28][29]. Of course, the educational system also plays a relevant role in shaping the perceptions of adolescents, as well as in the development of their potentialities and difficulties [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, authoritarian parenting has been associated with increased extraversion and openness, while authoritarian-inconsistent parenting has been linked to heightened extraversion, conscientiousness, agreeableness, and increased emotional stability ( Kugler et al, 2022 ). Ashraf et al (2018) also reported a causal relationship between parenting style and personality traits in primary school children. However, it is important to highlight that none of the existing research has explored the impact of parenting style on the Big Five personality traits of high school students.…”
Section: Introductionmentioning
confidence: 92%
“…Finally, only neuroticism was selected to examine its mediating effect between parental bonding and depression symptoms. Other personality traits such as extraversion have been found to be related to both parental bonding (49,50) and depression symptoms (51,52). Therefore, future studies should further explore the mediating role of extraversion in the relationship between parental bonding and depression symptoms.…”
Section: Limitationsmentioning
confidence: 98%